(untitled) (Research, Society and Development, 2021)
This project aimed to detail the analysis and gradual modeling of the development of an Application for classification of soybeans, corn, sorghum and beans, with the purpose of providing the producer with a tool that allows monitoring the process of classification of soybeans, corn, sorghum grains and bean. The producer is delegated the purpose of inserting data into the available tool, which processes the monitoring and monitoring of the grain classification process, so that it is possible for the producer to confront the results obtained by the Application, the generation of the reports to compare with that of the receiving organization. In this way, the objective is to ascertain in real time the classification of grains aimed at the desired producer, with regard to soy, corn, beans and sorghum, according to the standards legally instituted by regulations (beans 12/2008, corn 60/2011, soybean 11/2007 and sorghum ordinance 268/1984) of the Ministry of Agriculture, Livestock and Supply (MAPA) and also based on specialized literature. In the act of commercialization, the results of the Application referring to the general and specific database per lot that is generated, assisting at the end of the grain classification process in the reduction of disparities and losses of the lot.